ORGAN DONATION AND OWNERSHIP OF BODY PARTS: PROTECTION OF BODILY INTEGRITY - Kovačević, Dušica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Bodily integrity is one of the major areas of interest in organ transplantation. The transfer of one human organ from one body to another is an issue of the physical integrity of the human body. The focus of the work is on how to treat the human body in situations where it is necessary to make organ donation decisions both in its own and others’ best interests. In this context, the option of an equal right to bodily integrity is considered as is the option of ownership of the body. The final part of the paper draws conclusions about the roles that certain participants in the organ donation process should play in contemporary circumstances.